Coronary artery disease and cancer mortality in a cohort of workers exposed to vinyl chloride, carbon disulfide, rotating shift work, and o‐toluidine at a chemical manufacturing plant. Issue 4 (24th January 2014) - Carreón, Tania; Hein, Misty J.; Hanley, Kevin W.; Viet, Susan M.; Ruder, Avima M.
<x xml:space="preserve">Abstract</x> Background We updated through 2007 the mortality experience of 1, 874 workers employed at a New York State chemical manufacturing plant between 1946 and 2006. Methods Reassessed exposures to vinyl chloride, carbon disulfide, and shift work and categories of o‐toluidine exposure were based on year, department and job title. Standardized mortality ratios (SMR) compared mortality to that of the US population. Internal comparisons used directly standardized rate ratios. Results Hepatobiliary cancer mortality was elevated among workers ever exposed to vinyl chloride (SMR = 3.80, 95% confidence interval 1.89–6.80); directly standardized rates increased with increasing vinyl chloride exposure duration. No increase in non‐Hodgkin lymphoma mortality was observed with vinyl chloride and shift work exposures. Internal comparisons showed increased coronary artery disease mortality among long‐term workers exposed to carbon disulfide and shift work for 4 years or more. Conclusions Excess coronary artery disease mortality confirms earlier results; further investigation is needed to understand risk factors. Am. J. Ind. Med. 57:398–411, 2014. © 2014 Wiley Periodicals, Inc.